Agroecological Approach to Agricultural Sustainability, Food Sovereignty And Endogenous Circular Economy - Khanal, Nityananda; Thapa, Sushil (Nepal Public Policy Review, 2023)
The resource over-exploitative, waste-burdening, linear developmental model has transgressed the planetary safe operating limits of the earth systems engendering climatic emergencies and also exacerbated socioeconomic imbalances. The only way of mitigating these planetary and social crises is to formulate and strictly enact ecofriendly, resource recycling, circular economic, equitable, decentralized and peoples´ participatory developmental policies and practices. The objective of this review is to contribute to the discourse on transformative agriculture-centred, circular economic policies and practices that foster nature-based solutions and prudent extraction, use, re-use, and recycling of resources while minimizing waste and environmental externalities. The review highlights Nepal’s geophysical, agroecological and socioeconomic realities, their manifestations and policy implications. It also explores how past development policies have been mismatched with these realities, eroding the indigenous resource bases and knowledge systems, and thereby, disrupting the agriculture-based, self-reliant, and food sovereign livelihoods systems. The article argues that agroecology, as a science, practice and movement envisions a nature-based, circular economic and socially just transformative pathway towards sustainable agri-food systems embracing food sufficiency, safety and sovereignty. This pathway contributes to healthy people, healthy animals and healthy ecosystems, hence strengthening the vision of One Health. Building on the agroecological perspectives, this article presents the resynthesized eight operational elements referred to as “8-S-elements” for agroecological transformation. These elements pertain to the prudent management of space (S1), species (S2), seeds (S3), soils (S4), seasonality (S5) and stress factors (S6) through the synergistic integration of agroecosystems and livelihood systems components (S7) with socioeconomic rationality (S8). In the Nepalese context, as an agriculture-based economy, agri-food and livelihoods are viewed as complementary facets. This study recommends the transformative policy options based on the principles of ecological stewardship and socioeconomic objectivity.